Synthesis of an exceptional water-stable two-fold interpenetrated Zn(ii)-paddlewheel metal–organic framework1. Issue 31 (21st August 2015) - Wang, Jingjing; Zhang, Jun; Jin, Fengyan; Luo, Yanping; Wang, Shufen; Zhang, Zaiyong; Wu, Yong; Liu, Hongke; Lu, Jack Y.; Fang, Min
<x xml:space="preserve">Abstract</x> An exceptional water-stable two-fold interpenetrated Zn(ii)-paddlewheel metal–organic framework was obtained via the facile conversion of its non-interpenetrated isomer at ambient temperature, showing high CO2 and CH4 uptake capacities.